A novel dielectric tensiometer enabling precision PID-based irrigation control of polytunnel-grown strawberries in coir. (January 2018) - Goodchild, Martin S.; Jenkins, Malcolm D.; Whalley, William R.; Watts, Chris W.
Abstract : The benefits of closed-loop irrigation control have been demonstrated in grower trials which show the potential for improved crop yields and resource usage. Managing water use, by controlling irrigation in response to soil or substrate moisture changes, to meet crop water demands is a popular approach but requires substrate specific moisture sensor calibrations and knowledge of the moisture levels that result in water deficit or over-watering. The use of water tension sensors removes the need for substrate specific calibration and enables a more direct relationship with hydraulic conductivity. In this paper, we present a novel dielectric tensiometer that has been designed specifically for use in soil-free substrates such as coir, peat and Rockwool with a water tension measurement range of −0.7 kPa to −2.5 kPa. This new sensor design has also been integrated with a precision PID-based (drip) irrigation controller in a small-scale coir substrate strawberry growing trial: 32 strawberry plants in 4 coir growbags under a polytunnel. The data illustrates that excellent regulation of water tension in coir can be achieved which delivers robust and precise irrigation control - matching water delivery to the demands of the plants. During a 30-day growing period vapour pressure deficit (VPD) and daily water use data was collected and the irrigation controller set to maintain coir water tension at the following levels: −0.90 kPa, −0.95 kPa and −1 kPa for at least 7 consecutive days at each level. For each set-point the coir water tension was maintained by the irrigation controller to within ±0.05 kPa. Meanwhile the polytunnel VPD varied diurnally from 0 to a maximum of 5 kPa over the trial period. Furthermore, the combination of the dielectric tensiometer and the method of PID-based irrigation control resulted in a linear relationship between daily average VPD and daily water use over 10 days during the cropping period. Highlights: A novel dielectric tensiometer sensor for use in high porosity soil-free substrates. Sensor measurement range of −0.7 kPa to −2.5 kPa. Sensor with precision PID irrigation controller achieves ±0.05 kPa control in coir. Precise regulation of water tension achieved over a wide range of VPD. Stable water status enables daily water use to be correlated with average daily VPD.